International economics - Södersten, Bo. (London : Macmillan, 1970)
The purpose of this book is to present a reasonably rigorous, modern treatment of international economics which should still be accessible to undergraduate students and persons with general interest in economics and international affairs.
Includes bibliographical references and index.
ijb 18/07/2018
Loans
Keywords: International affairs; Economics